Unusual Large Parosteal Lipoma of the Proximal Forearm: A Case Report and Literature Review - Abdullah K. Ghafour; Saywan K. Asaad; Soran S. Raoof; Rezheen J. Rashid; Rebaz M. Ali; Hiwa O. Abdullah; Abdullah A. Qadir; Shvan H. Mohammed; Lawen Jamal Mustafa; Fahmi H. Kakamad (Case Reports in Orthopedics)
Conclusion: The tumor is a rare osseous neoplasm that may remain asymptomatic for years until it reaches a size capable of exerting pressure and causing motion difficulty. Meticulous care is paramount during surgical management to prevent iatrogenic nerve injury.